Including past and ongoing dynamics in ex ante project research - Burg, Margreet van der (Wageningen University & Research, 2023)
Many projects start with a baseline setting the state of affairs or a needs assessment with community members and/or key persons. Only few ex ante studies have sought to include past and ongoing dynamics. This is especially concerning for projects aiming at gender-transformative change since these cannot rely on literature about localized changes as in gender and other social relations, labor divisions or use of introduced innovations. We might wonder why such ex ante research covering the momentum is never really disputed. And what methodologies can we use to change? First, I illustrate why it is necessary to systematically contextualize any project not only within its local spatial-geographical, ecologicalclimatological, and social-cultural context but also its temporal-historical one. I will also elaborate on the need for decolonizing the underlying bias toward ‘distant’ cultures and communities as long-time homogeneous, unspoiled, stable and hardly changed, especially in rural areas. Second, I will show and build on existing approaches that include past and ongoing dynamics in their project sites. These are, for instance, the CGIAR GENNOVATE project tools that help ranking change over 10 years, and mapping exercises to make changes visible as an entry point to elaborate on the experiences with and perceptions on change in relation to various impacts. Additional local sources are community elders or local newspapers. Significant themes to focus on are project dependent and can be extracted from historical and development literature. By purposefully including participants in their long-term processes of change and building on their local experiences and learning with changes and their impacts, transformative change will be more within reach.